Effects of MDMA (Ecstasy) on Oocyte Quality and Fertilization Rate in Mice - F Haji- Maghsoudi; MA Khalili; A Karimzade (JRI, 2010)
Introduction: Ecstasy drug abuse is relatively common among the youth undergoing psychosocial stresses. Categorized as a stimulant drug, ecstasy has nervous, cardiac and immunological side-effects. The endocrine system is not spared from the harmful effects of the drug and it could influence ovulation by exerting its effects on the hypothalamic-hypophyseal-gonadal axis. The aim of this study was to evaluate the effects of ecstasy on the quality of oocytes and on fertilization rate in mice. Materials and Methods: Thirty female NMRI mice were divided into three groups, after checking for their estrous cycles. At the beginning of each cycle, ecstasy was administered intraperitoneally to the animals in groups A (a minimum dose of 5 mg/kg/day) and B (a maximum dose of 20 mg/kg/day). At the end of the second day, 10 IU PMSG, and at the end of the 4th day, 10 IU HCG were administered intra-peritoneally. The mice in group C underwent the same procedures except receiving ecstasy. All the mice were sacrificed on the fifth day to aspirate their oocytes for further evaluation. In-vitro fertilization was done using mature or MII oocytes and fertilization was checked after 5 hours. The results were later statistically analyzed. Results: The number of retrieved oocytes was similar between the experimental and control groups. However, the rate of mature oocytes (MII) was significantly higher (p = 0.0001) in the controls (31.2%) than the mice in groups A (15.2%) and B (12.8%). Moreover, fertilization rate was significantly higher in the controls than the experi-mental groups. Conclusion: Administration of Ecstasy in mice can affect both oocyte maturity and the fertilization potential of oocytes. The overall effects of ecstasy on embryo devel-opment and implantation needs further studies to reach a definitive conclusion.
Keywords: Ecstasy, Oocyte, Ovary, Fertilization, In Vitro fertilization, Beta-keto-3,4-methylenedioxymethamphetamine (MDMA), Fertility, Methamphetamine